SOSIALISASI MANAJEMEN DIGITAL MARKETING MENGGUNAKAN BLOG PADA UMKM JASA PENJAHIT BAJU DI DUSUN PESISIR BARAT PANTAI CAMPLONG KABUPATEN SAMPANG - Wahyu Liana; Faisol, Faisol (Fakultas Pertanian, 2024)
The problems faced by this clothing sewing business are that partners do not focus enough on developing marketing management, partners rely more on conventional marketing systems, and the business location is not very strategic. This makes it difficult for their business to be known by the wider community, which becomes an obstacle in developing their business. This activity aims to provide a solution to the problems being faced, namely by implementing marketing management using internet media (online). With the socialization and training of online marketing management, it is hoped that it will broaden the insight of MSMEs in utilizing the internet as an online promotional medium to introduce their business to the wider community and increase their business turnover. The result of this activity is that business actors in the clothing sewing service sector in the Pesisir Barat hamlet of Camplong Beach have knowledge in using social media and the internet as a means to promote their business.